2017
DOI: 10.1039/c6ta09547j
|View full text |Cite
|
Sign up to set email alerts
|

Serpent-cactus-like Co-doped Ni(OH)2/Ni3S2 hierarchical structure composed of ultrathin nanosheets for use in efficient asymmetric supercapacitors

Abstract: A Co-doped Ni(OH)2/Ni3S2 hybrid was grown in situ on Ni foam (NiCo-10) via a one-pot hydrothermal reaction with two-step temperature control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(26 citation statements)
references
References 62 publications
1
25
0
Order By: Relevance
“…At a high current density of 20 mA cm −2 , its energy density still retained 86.6 Wh kg −1 with a power density of 9.138 kW kg −1 . The Ni/Ni 3 S 2 @NiMoO 4 //AC cell can deliver a power density of 18.277 kW kg −1 with a specific energy density of 80.7 Wh kg −1 at the current density of 40 mA cm −2 , The maximum capacitive performance of our hybrid device is substantially higher than that of many previously reported Ni 3 S 2 and NiMoO 4 ‐based electrode materials, such as Ni 3 S 2 @PPy//AC (17.54 Wh kg −1 at the power density of 179.3 W kg −1 ), ZnCo 2 O 4 /NiMoO 4 //AC (40.0 Wh kg −1 at the power density of 1050.2 W kg −1 ), Co‐doped Ni(OH) 2 /Ni 3 S 2 //AC (51.5 Wh kg −1 at the power density of 825 W kg −1 ), Ni 3 S 2 //AC (34.6 Wh kg −1 at the power density of 105.4 W kg −1 ) . More comparison with other works were provided in Tables S1 and S2 (Supporting Information).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…At a high current density of 20 mA cm −2 , its energy density still retained 86.6 Wh kg −1 with a power density of 9.138 kW kg −1 . The Ni/Ni 3 S 2 @NiMoO 4 //AC cell can deliver a power density of 18.277 kW kg −1 with a specific energy density of 80.7 Wh kg −1 at the current density of 40 mA cm −2 , The maximum capacitive performance of our hybrid device is substantially higher than that of many previously reported Ni 3 S 2 and NiMoO 4 ‐based electrode materials, such as Ni 3 S 2 @PPy//AC (17.54 Wh kg −1 at the power density of 179.3 W kg −1 ), ZnCo 2 O 4 /NiMoO 4 //AC (40.0 Wh kg −1 at the power density of 1050.2 W kg −1 ), Co‐doped Ni(OH) 2 /Ni 3 S 2 //AC (51.5 Wh kg −1 at the power density of 825 W kg −1 ), Ni 3 S 2 //AC (34.6 Wh kg −1 at the power density of 105.4 W kg −1 ) . More comparison with other works were provided in Tables S1 and S2 (Supporting Information).…”
Section: Resultsmentioning
confidence: 77%
“…The intense Ni 3+ peaks indicate that the majority of Ni element in the final product is Ni 3+ cations. In the S 2p spectra (Figure c), the peaks at ≈162.1 and 163.3 eV and the satellite peak at ≈168.0 eV stem from S in the Ni 3 S 2 phase . For Mo 3d in Figure d, two peaks located at 235.2 and 232.1 eV with a splitting of 3.1 eV demonstrate the presence of Mo 6+ oxidation state.…”
Section: Resultsmentioning
confidence: 88%
“…[ 140 ] For example, Ye et al designed a binder‐free Co‐doped Ni(OH) 2 /Ni 3 S 2 hybrid cathode which delivered an ultrahigh specific capacitance value of 3023.4 F g −1 at 1 A g −1 and a superb rate performance. [ 141 ] Jampani et al developed Ti‐doped VO 2 via chemical vapor deposition (CVD) technique. [ 67 ] Theoretical studies demonstrated the substantial improvement in the electronic conductivity of the VO 2 was due to Ti doping and oxygen vacancies, which further elevated the capacitance value as high as 310 F g −1 .…”
Section: Heterogeneous Ion Doping Strategymentioning
confidence: 99%
“…Except for nonmetallic elements, doping with metal elements can also boost the electrochemical performance of electrode materials . Ye et al designed a Co‐doped Ni(OH) 2 /Ni 3 S 2 hybrid nanomaterial grown on Ni foam .…”
Section: Methods To Boost Capacitancementioning
confidence: 99%
“…Except for nonmetallic elements, doping with metal elements can also boost the electrochemical performance of electrode materials . Ye et al designed a Co‐doped Ni(OH) 2 /Ni 3 S 2 hybrid nanomaterial grown on Ni foam . As an electrode, the binder‐free Co‐doped Ni(OH) 2 /Ni 3 S 2 electrode exhibited an ultrahigh specific capacitance value of 3023.4 F g −1 at 1 A g −1 and a superb rate performance.…”
Section: Methods To Boost Capacitancementioning
confidence: 99%